Kill Red - O'Hara, Max (O'Hara, Max. Wolf Stockburn, Railroad Detective, 2022)
Riding the rails across America's uncivilized and unpredictable western frontier requires true grit. For Wolf Stockburn, Railroad Detective, it takes a keen eye, quick draw, and dead aim to protect passengers from the most dangerous outlaws in the west - or avenge them... Red Miller is more than a thief and a killer. He robs banks and trains not just for the money, but to spit in the eye of every badge-toting lawman who dares enforce law and order. He surrounds himself with only the deadliest of desperadoes - and takes a perverse pleasure in deadly bloodshed. Five of those people have banded together. They have all lost something to Red's murderous rampage. There is no place in America or Mexico where the bandit and his gang can hide from their vengeance. And they're led by Wolf Stockburn,Wells Fargo detective and a dead shot who knows that sometimes justice comes only from the barrels of smoking guns.